1983
DOI: 10.1002/ar.1092050302
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lesions of suprachiasmatic nuclei affect circadian rhythms in [3H]‐thymidine incorporation into deoxyribonucleic acid in mouse intestinal tract, mitotic index of corneal epithelium, and serum corticosterone

Abstract: Investigations into the role of the suprachiasmatic nuclei (SCN) in the coordination of circadian rhythms have presented differing results. Several reports have shown that ablation of the suprachiasmatic nuclei (SCNA) alters the phase and amplitude of rhythms but does not abolish them. The present study investigates the effect of SCNA on the rhythms in cell proliferation in various regions of the intestinal tract as measured by the incorporation of [3H]-thymidine into deoxyribonucleic acid, in the mitotic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For example, the period of the cell cycle could be regulated by the 24-h rhythm of body temperature or hormone levels controlled by the SCN. The phase and amplitude of rhythms of cell division are altered in SCN-lesioned mice, suggesting that the circadian system can regulate cell proliferation in vivo (56). A previous study also showed that the circadian rhythm of circadian gene mutant primary fibroblasts acquired the periodicity of the host rhythm when the fibroblasts were transplanted into wild-type mice (57).…”
Section: Resultsmentioning
confidence: 96%
“…For example, the period of the cell cycle could be regulated by the 24-h rhythm of body temperature or hormone levels controlled by the SCN. The phase and amplitude of rhythms of cell division are altered in SCN-lesioned mice, suggesting that the circadian system can regulate cell proliferation in vivo (56). A previous study also showed that the circadian rhythm of circadian gene mutant primary fibroblasts acquired the periodicity of the host rhythm when the fibroblasts were transplanted into wild-type mice (57).…”
Section: Resultsmentioning
confidence: 96%
“…3 H]-thymidine incorporation into the DNA of different organs (tongue, esophagus, gastric stomach, and colon) and of the mitotic index of the corneal epithelium of female BD2Fl mice after bilateral lesioning of the suprachiasmatic nuclei was later demonstrated [29] . The most consistent result was a phase advance in the rhythms in cell proliferation in the tongue, esophagus, gastric stomach, colon, and corneal epithelium, and a reduction in the circadian amplitude detected in the tongue, esophagus, and corneal epithelium.…”
Section: Suprachiasmatic Nuclei Circadian Rhythms and Agingmentioning
confidence: 99%
“…Even the suprachiasmatic nuclei (SCN) do not seem to be indispensable for rhythmic divisions to occur in synchrony in mouse intestine or corneal epithelium (Scheving et al 1983), as well as in mouse bone marrow (Filipski et al 2004a). In a study involving 52 mice with histologically proven SCN ablation and 34 sham-operated controls kept under LD 12:12 synchronization, the rest-activity cycle was suppressed in all of the mice with SCN ablation whereas the plasma corticosterone rhythm persisted yet with a nonsinusoidal pattern, a damped amplitude, and a phase-advance by a few hours (Filipski et al 2004a).…”
Section: Circadian Gating Of Cell Divisionmentioning
confidence: 99%